Reading women : literacy, authorship, and culture in the Atlantic world, 1500-1800 - Kelly, Catherine E.; Brayman Hackel, Heidi (Material texts., 2008)
Reading Women brings into conversation the latest scholarship by early modernists and early Americanists on the role of gender in the production and consumption of texts during the expansion of female readership in the early modern period.